Monetary circulation in the General Captaincy of Cuba during the eighteenth century (Tzintzun, Revista de Estudios Históricos, 2019)
In the eighteenth century the island of Cuba remained a strategic point in the system of the Spanish Silver Fleet. Even as recipient of an important cash subsidy of the Viceroyalty of New Spain, it requested the issuance of a provincial copper currency, which eventually was coined during the War of Jenkins’ Ear, and the problems related to the lack of circulation maintained throughout the century. It is also studied in this paper the currency in circulation in the dependent territories of Florida and Louisiana.